Antibacterial Activities of Methanolic Bark Extracts of Berberis aristata and Berberis asiatica from Different Elevations of Champadevi Hill, Nepal - Awal, Rajeena; Pant, Deepak Raj; Joshi, Giri Prasad (Nepalese Journal of Agricultural Sciences, 2025)
Berberis is the largest genus of the family Berberidaceae which grows in almost all vegetation type throughout Nepal from 1000-4600 m. Most of the Berberis species found in Nepal have medicinal uses. Methanolic extracts of B. aristata collected from two elevations (1900 and 2400 m) and B. asiatica from three different elevations (1400 m, 1900 m and 2400 m) were analyzed for antibacterial activities against four bacterial strains (ATCC). Agar well diffusion technique was used for antibacterial screening and inhibition was observed for plant extracts of different concentrations ranged from 6.25 mg/ml to 100 mg/ml, Gentamycin (+ve control), and DSMO (-ve control). Methanolic extracts from both species from different elevations showed antibacterial activity against gram positive (Staphylococcus aureus and Staphylococcus epidermidis) as well as gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa). Antibacterial activity was found decreased with increase of elevation for almost all concentrations of bark extracts from both Berberis species. However, comparison between antibacterial activities of bark extracts from two elevations (1900m and 2400m) against all bacterial strains except E. coli showed higher ZOI for B. asiatica. In case of E. coli, the higher ZOI was obtained for B. aristata. The results of the present study supported the idea that production of secondary metabolites in plants against microbes depends on possibility of infection which is more or less high in lower elevations in comparison to higher elevations.